2019
DOI: 10.1037/xge0000611
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of exceptions? Examining representations of regular and exceptional category members across development.

Abstract: Evidence from multiple category learning studies suggest that exceptions to a category rule are remembered better than the items that follow that rule (Davis, Love, & Preston, 2012;Palmeri & Nosofsky, 1995;Sakamoto & Love, 2004). Based on differences in recognition memory, it has been suggested that category exceptions may be represented separately from regular category members. Here, we present 4 experiments investigating representations of regular and exceptional category members as well as potential develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In line with these predictions, infants' ability to learn categories is found to be affected by the level of category coherence, with less coherent categories being more difficult (Gómez & Lakusta, 2004;Younger, 1990;Younger & Gotlieb, 1988). Moreover, young children demonstrate poorer memory for category exceptions than for typical category members (Savic & Sloutsky, 2019).…”
Section: Hippocampal Maturation and Development Of Categorization Abilitiesmentioning
confidence: 56%
“…In line with these predictions, infants' ability to learn categories is found to be affected by the level of category coherence, with less coherent categories being more difficult (Gómez & Lakusta, 2004;Younger, 1990;Younger & Gotlieb, 1988). Moreover, young children demonstrate poorer memory for category exceptions than for typical category members (Savic & Sloutsky, 2019).…”
Section: Hippocampal Maturation and Development Of Categorization Abilitiesmentioning
confidence: 56%
“…Along these lines, Sloutsky and Fisher (2004) have shown that when making inferences about the pictures of animals, children were more oriented to items themselves, rather than their categories, remembering individual items better than adults when asked to think about the objects at the level of the category. Furthermore, children are equally sensitive to features that are diagnostic to category membership and those that are not, whereas adults prioritize diagnostic features when learning categories (Deng & Sloutsky, 2015; Savic & Sloutsky, 2019). In the current study, however, we did not find support for an orientation toward item‐level information in children in the domain of statistical learning.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of an effect in the TR condition, however, seems more puzzling and could be related to the presence of atypical items in general or less effective reward learning, as it appeared that reward generalization was concurrently absent in the GCM group of the TR condition. However, given the exploratory nature of Study 3, and the ongoing debate regarding the special role of atypical items (or exceptions) in memory and their implications for the representation of categories (e.g., Erickson & Kruschke, 1998; Nosofsky et al, 1994; Poldrack et al, 2001; Poldrack & Foerde, 2008; Savic & Sloutsky, 2019; Schlegelmilch, Wills, & von Helversen, 2018), these explanations should be considered speculative, and further research is needed to disentangle the effects of typicality and item rewards.…”
Section: Discussionmentioning
confidence: 99%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. Nosofsky et al, 1994;Poldrack et al, 2001;Poldrack & Foerde, 2008;Savic & Sloutsky, 2019;Schlegelmilch, Wills, & von Helversen, 2018), these explanations should be considered speculative, and further research is needed to disentangle the effects of typicality and item rewards.…”
Section: Boundary Conditions Rules and Exceptionsmentioning
confidence: 99%